UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN EKONOMI MELALUI PEMBELAJARAN KOOPERATIF STAD - Ariyani, Windi; Saryantono, Buang; Idham, M (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
The problem of this research is low student learning outcomes in class economic subjects XI IPS 1 SMA Al Azhar 3 Bandar Lampung that is only 6 students (20,69%) of 29 who were able to reach KKM. Where the KKM value SMA Al Azhar 3 Bandar Lampung is 78. The purpose of this study was to improve student learning outcomes on economic subjects using STAD (student team achievement division) type cooperative learning. The method used is classroom action research (PTK) carried out with 2 cycles. Each cycle consists of 4 stages namely planning, action, observation, and reflection. Data collection used is test, observation, interview, and documentation. The results of this study indicate an increase in activity and student learning outcomes, namely for student learning activities cycle 1 in large 6,55% and in cycle 2 to 9,83%. Then for student learning outcomes in the first cycle the highest score 85 and lowest score 45 with an achieved completeness by 48,28% of all student. In the second cycle the highest score 95 and lowest score 65 with an achieved completeness by 82,76% of all student. Increase in completeness of learning outcomes in cycle 1 to cycle 2 by 34,48%